Free temporal fascia flap to cover soft tissue defects of the foot: a case report - Schreiber, Martin (GMS Interdiscip Plast Reconstr Surg DGPW, 2015)
Severe soft tissue defects as a result of lye contamination remain a huge challenge in the interdisciplinary approach of trauma surgeons and plastic surgeons. Free tissue transfer is a suitable surgical option for successful reconstruction of form and function of defects in the distal parts of the lower extremities. We report the successful two-stage reconstruction of a full thickness lye contamination at the dorsum of the foot with a free temporoparietal fascia flap covered with a split-thickness skin graft from the thigh. The described method is a suitable operative alternative to anterolateral thigh flaps or other thin fascia flaps regarding flap harvest and donor site morbidity and should be considered in the portfolio of the plastic surgeon.